Work organization of medical establishments at different stages of medical support of the rural population : methodical recommendations to prepare 3–4 year students for practical classes for the discipline of «Social Medicine, organization of health care» [Electronic resourсe] - Bobrova, Oksana Vyacheslavivna; Tsukor, Nataliia Hryhorivna; Боброва, Оксана Вячеславівна; Цукор, Наталія Григорівна (Kharkiv : V.N. Karazin Kharkiv National University, 2024)
The presented methodological recommendations for those seeking higher education highlight topics devoted to an important section of social medicine and health care organization - the organization of the work of medical and preventive institutions at various stages of medical provision of the rural population. The methodical recommendations were developed on the basis of the current regulatory documents regarding the reform of health care of Ukraine. The stages of providing medical care to the rural population, the essence of stages, as well as the main regulatory and legal documents regulating the activity of health care facilities in the conditions of health care reform, their list and content are described. The methodological recommendations are made in accordance with the educational and professional training program for higher education applicants of the medical faculty of the 3rd-4th year of the university, qualification level Master, in the field of knowledge 22 «Health care», specialty 222 «Medicine». The material in the methodical recommendations is presented in English.

У представлених методичних рекомендаціях для здобувачів вищої освіти висвітлені теми, присвячені важливому розділу соціальної медицини та організації охорони здоров`я – oрганізації роботи лікувально-профілактичних закладів на різних етапах медичного забезпечення сільського населення. Методичні рекомендації розроблені на основі діючих нормативних документів щодо реформування охорони здоров'я України. Описані етапи надання медичної допомоги сільському населенню, сутність етапності, а також основні нормативно-правові документи, що регламентують діяльність ЛПЗ в умовах реформування охорони здоров'я, їх перелік і зміст. Методичні рекомендації складені відповідно до освітньо-професійної програми підготовки здобувачів вищої освіти медичного факультету 3-4 курсу університету, кваліфікаційного рівня Магістр, в галузі знань 22 «Охорона здоров’я», спеціальність 222 «Медицина». Матеріал у методичних рекомендаціях викладений англійською мовою.
Організація роботи лікувально-профілактичних закладів на різних етапах медичного забезпечення сільського населення : методичні рекомендації до практичних занять для здобувачів вищої медичної освіти 3–4 року навчання з дисципліни «Соціальна медицина, організація охорони здоров’я» [Електронний ресурс]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі
Keywords: MEDICINE; medical and preventive care for the rural population; stages of medical care; family medicine; outpatient medical care for the rural population; inpatient medical care for the rural population; emergency medical care for the rural population; лікувально-профілактична допомога сільському населенню; етапи медичної допомоги; сімейна медицина; амбулаторна медична допомога сільському населенню; стаціонарна медична допомога сільському населенню; екстрена медична допомога сільському населенню